THE MINIMUM WAGE IMPACT ON LABOUR PRODUCTIVITY: THE CASE OF SELECTED SEE COUNTRIES - Trenovski, Borce; Kozeski, Kristijan; Tashevska, Biljana; Peovski, Filip (Research Centre in Public Administration and Public Services, Bucharest University of Economic Studies, 2021)
Increasing the statutory minimum wage in most SEE economies, in the same time represents an increase in the main source of income, and providing a higher level of welfare for workers. However, in some SEE countries, despite the unsuitable economic indicators, and the slow recovery from the economic crisis, a sharp increase in the minimum wage is observed. The increase in these countries contributes to the growing part of the workers who receive minimum wage, which additionally burdens the economic system. In addition, the increase of the minimum wage should not be a substitute for the improvement of the conditions on the labor market and the labor market institutions, as well as the insignificant increase of the labor productivity that persistently fails to catch up with the increase of the labor productivity in Western Europe countries. In the previous period, on the example of Bulgaria, Romania, Croatia, North Macedonia, Albania and Serbia, there was a significant increase in the level of the statutory minimum wage. These countries, as economies in which in the previous period the highest rate of increase of the minimum wage was observed, will be the subject of research. Hence, a relationship analysis was conducted between the statutory minimum wage and labour productivity, using a panel-regression model. The countries are divided in two groups: non-EU member countries (North Macedonia, Albania and Serbia) and EU member countries (Bulgaria, Romania and Croatia). These groups are formed according to specific economic criteria (level of GDP and labour mobility) and non-economic criteria (EU membership). The aim of the paper is to discover the correlation and causal relationship between an increase in the statutory minimum wage and labour productivity. The results provide an indicative picture of how governments set the minimum wage, the extent of their increasing, and whether the increase in the minimum wage is to some extent related to the increase in labor productivity. The results indicate that in the first group of countries (North Macedonia, Albania and Serbia) the relationship between statutory minimum wage and labour productivity is strong and positive. Contrary, this relationship is weak and negative in the countries from the second group (Bulgaria, Croatia and Romania). The correlation analysis results are consistent with the estimates from the panel – regression.
Keywords: minimum wage, calculation of the minimum wage according to (ILO), Macedonia, average wage, comparative analysis.; labor productivity, economic growth, South Eastern Europe; Comparative Analysis; panel regression